2016
DOI: 10.1007/s12291-016-0631-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of LCAT and Apo A-I in Newly Diagnosed HIV Patients

Abstract: Human immunodeficiency virus (HIV) infection is a growing concern for health workers. The two major components of dyslipidemia in HIV infected patients are hypertriglyceridemia and decreased levels of high density lipoprotein (HDL) which contribute to increased atherosclerotic risk. The study included 150 newly diagnosed HIV patients and 150 healthy controls. In all these cases Lecithin cholesterol acyl transferase (LCAT) activity was assessed by measuring the difference between esterified and free cholesterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Mechanistically, elevated bacterial lipopolysaccharide (LPS) binding LP complexes using a Salmonella model ( Salmonella minnesota R595 125 I-labeled LPS) to evaluate initiation of atherogenic plaque formation showed that LPS-LP fractions in complex formation as an risk factor for initiating atherosclerosis in hypercholesterolemia ( Schwartz and Dushkin, 2002 ). Furthermore, two other major components of dyslipidemia, namely, hypertriacylglycerolemia and decreased levels of HDL, which also contributes to increased atherosclerotic risk, have been observed in individuals with HIV ( Mirajkar et al, 2017 ). These dyslipidemic changes are attributed to decreased LCAT activity together with a decline in apo A-I levels leading to a reduction in the reverse cholesterol transport ( Mirajkar et al, 2017 ).…”
Section: Modulators Of Host Lcat Activity By Bacteria Viruses and Fungimentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistically, elevated bacterial lipopolysaccharide (LPS) binding LP complexes using a Salmonella model ( Salmonella minnesota R595 125 I-labeled LPS) to evaluate initiation of atherogenic plaque formation showed that LPS-LP fractions in complex formation as an risk factor for initiating atherosclerosis in hypercholesterolemia ( Schwartz and Dushkin, 2002 ). Furthermore, two other major components of dyslipidemia, namely, hypertriacylglycerolemia and decreased levels of HDL, which also contributes to increased atherosclerotic risk, have been observed in individuals with HIV ( Mirajkar et al, 2017 ). These dyslipidemic changes are attributed to decreased LCAT activity together with a decline in apo A-I levels leading to a reduction in the reverse cholesterol transport ( Mirajkar et al, 2017 ).…”
Section: Modulators Of Host Lcat Activity By Bacteria Viruses and Fungimentioning
confidence: 99%
“…Furthermore, two other major components of dyslipidemia, namely, hypertriacylglycerolemia and decreased levels of HDL, which also contributes to increased atherosclerotic risk, have been observed in individuals with HIV ( Mirajkar et al, 2017 ). These dyslipidemic changes are attributed to decreased LCAT activity together with a decline in apo A-I levels leading to a reduction in the reverse cholesterol transport ( Mirajkar et al, 2017 ). Similar findings were reported for hepatitis C virus (HCV) infections ( Blaising and Pécheur, 2013 ) ( Figure 7 ).…”
Section: Modulators Of Host Lcat Activity By Bacteria Viruses and Fungimentioning
confidence: 99%